2011
DOI: 10.1177/1010539511399119
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening

Abstract: To assess the awareness and acceptability of colorectal cancer (CRC) screening in noncompliant Singaporeans and to determine if their barriers can be overcome by education. A questionnaire developed from thematic analysis of open-ended interviews with 72 subjects was administered to 580 residents in a local high-rise housing estate. Participants aware of CRC screening were assessed for barriers and acceptability of CRC screening. All participants were subsequently educated about CRC screening and reassessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…While there are few effective methods to tackle the psychological barriers, Sung et al [6] has recommended the use of lay health advisors who have previously recovered from CRC, as this gives the population a more relatable person. As for defeatist beliefs, some studies have reported success in the usage of interventions that are culturally orientated and faith based [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While there are few effective methods to tackle the psychological barriers, Sung et al [6] has recommended the use of lay health advisors who have previously recovered from CRC, as this gives the population a more relatable person. As for defeatist beliefs, some studies have reported success in the usage of interventions that are culturally orientated and faith based [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al [6], Farooqui et al [7], Loh et al [10], Yusoff et al [11], Harmy et al [12], Foo et al [14], Javadzade et al [16], Wong et al [23], Khayyat et al [17], Tastan et al [18], Wong et al [24], Abdullah et al [21], Ahmad [22] 13 'Ostrich strategy'-aversion to facing test results Sung et al [16], Loh et al [10], Yusoff et al [11], Harmy et al [12], Foo et al [14], Javadzade et al [16], Wong et al [23], Bae et al [25], Tastan et al [18], Wong et al [24], Ahmad [22] 11 Financial constraints, lack of insurance coverage Sung et al [6], Farooqui et al [7], Yusoff et al [11], Koo et al [5], Harmy et al [12], Foo et al [14], Deng et al [15], Wong et al [23], Tastan et al [18], Wong et al [24], Abdullah et al [21], Ahmad [23] study subjects, who comprised of Chinese people, were partly attributable to the cultural aversion towards topics regarding the bowel, displaying fecal aversion behavior. This is particularly eminent among the elderly folk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Yong Loo Lin School of Medicine, National University of Singapore, medical students in the fourth year of a 5 year bachelor of medicine and bachelor of surgery degree embark on a research project over a year in a module called the Community Health Project (CHP), supervised by faculty members from the Saw Swee Hock School of Public Health in the same university. The CHP is a capstone research project in which groups of medical students (of 25–40 students each) work on a clinical, public health, epidemiologic or health services research project with the ultimate goal of better understanding and improving the health status of their target population, and which is often published (for examples see Wee et al [ 9 ], Foo et al [ 10 ], Lee et al [ 11 ] or Koo et al [ 12 ]). Medical students are expected to integrate and apply what they have learned from basic sciences, clinical sciences, epidemiology, public health and biostatistics since the start of medical school in their CHP.…”
Section: Methodsmentioning
confidence: 99%